(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Intradural extramedullary spinal cord tumours (IESCT) accounts for approximately two thirds of all intraspinal neoplasm and are of important clinical consideration and surgery is the essence in cases with neurological deterioration. Objective: To share our experience on the outcome of surgical excision of intradural extramedullary spinal cord tumours. Methods: Results of 60 patients surgically treated intradural extramedullary spinal tumours between October 2003 and October 2015 at Bangabandhu Sheikh Mujib Medical University and in our private settings, Dhaka, were analyzed retrospectively. There were 32 males, 28 females with an average age of 52.4 years (13-70 years) and followed up for at least a year. The preoperative symptom with duration, tumours location and intradural space occupancy and the histopathological diagnosis were analyzed. Pain was evaluated by the visual analogue scale (VAS) and the neurologic function was assessed by Nurick’s grade. Results: The tumours were located as, thoracic 32 (53.33%), lumbar 16 (26.67%), cervical 04 (6.67%), and junctional 08 (13.33%), CervicoThoracic-01, Thoracolumbar-07). The histopathological diagnosis included schwannoma 35 (58.33%), meningiomas 14 (23.33%), neurofbroma 4 (6.67%), arachnoid cyst and myxopapillary ependymoma 03 (05.00%) each and paraganglioma 01 (01.67%). The VAS score was reduced in all cases from 8.0 ± 1.2 to 1.2 ± 0.8 (p < 0.003) and the Nurick’s grade was improved in all cases from 3.0 ± 1.3 to 1.0 ± 0.0 (p < 0.005). The preoperative neurological deficit improved within 8 postoperative weeks in most cases and within 1 postoperative year in all cases. Complications included cerebrospinal fluid leakage, parasthesia, dependant bedsore 02 (3.33%) each and recurrence 03 (05.00%). and further neurological deterioration 1 (01.67%) case. Conclusion: lntradural extramedullary tumors detected by MRI are mostly benign and good clinical results can be obtained when treated surgically. Aggressive surgical excision potentially minimizes neurologic morbidity and improved outcome.